Efficacy and Safety of Semaglutide for the Management of Obese Patients With Type 2 Diabetes and Chronic Heart Failure in Real-World Clinical Practice - Pérez-Belmonte, Luis M.; Sanz-Cánovas, Jaime; García de Lucas, María D.; Ricci, Michele; Avilés-Bueno, Beatriz; Cobos-Palacios, Lidia; Pérez-Velasco, Miguel A.; López-Sampalo, Almudena; Bernal-López, M. Rosa; Jansen-Chaparro, Sergio; Miramontes-González, José P.; Gómez-Huelgas, Ricardo (Frontiers in Endocrinology, 2022)
Backgroundː The impact of glucagon-like peptide-1 receptor agonists on patients with heart failure has not been fully described. Our main objective was to evaluate the safety and clinical and glycaemic efficacy of once-weekly semaglutide in obese patients with type 2 diabetes and heart failure. Methodsː In this observational, retrospective, real-world study, we enrolled outpatients with type 2 diabetes, obesity, and heart failure who started semaglutide and were followed-up on at 3, 6, and 12 months. Resultsː A total of 136 patients were included. From baseline to 12 months, there was a significant improvement on the Kansas City Cardiomyopathy Questionnaire total symptom score (59.0 ± 24.1 vs 79.9 ± 28.4 points, p<0.01), a reduction in the proportion of patients with New York Heart Association functional class III (40.4% to 16.2%, p<0.01), and a reduction in N-terminal pro-brain natriuretic peptide levels (969.5 ± 653.5 vs 577.4 ± 322.1 pg/mL, p<0.01). Emergency department visits due to heart failure, hospitalizations due to heart failure, and all-cause hospitalizations also declined. Additionally, significant reductions in glycated hemoglobin (-1.4%) and body weight (-12.7 kilograms) were observed as well as a de-intensification of antidiabetic therapy. Moreover, semaglutide was safe and well-tolerated. Conclusionː In obese patients with type 2 diabetes and heart failure, the use of once-weekly semaglutide was safe and clinically efficacious, improving health and functional status. Nevertheless, more strong evidence on glucagon-like peptide-1 receptor agonists in heart failure is required.